2009
DOI: 10.1007/s10103-008-0638-z
|View full text |Cite
|
Sign up to set email alerts
|

Management of deep-seated malformations with photodynamic therapy: a new guiding imaging modality

Abstract: Photodynamic therapy is an emerging technology and results from the interactions between a photosensitiser, oxygen and light. The delivery of light may either be by surface illumination or by interstitial application. We describe the first clinical application of ultrasound-guided interstitial photodynamic therapy (US-iPDT). A total of 23 treatments with meta-tetra-hydroxyphenyl chlorine (mTHPC) and ultrasound-guided interstitial photodynamic therapy were performed on 21 patients with various conditions at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…The studies following showed similar results concerning CR rates (ranging from 0 % to 77%) . The overall complete remission rate calculated from the mentioned studies was 29% (114/399 patients). Figure shows an example of a patient with a locally advanced adenoid cystic carcinoma of the right paranasal sinuses, who was treated with interstitial PDT under MR image guidance.…”
Section: Clinical Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The studies following showed similar results concerning CR rates (ranging from 0 % to 77%) . The overall complete remission rate calculated from the mentioned studies was 29% (114/399 patients). Figure shows an example of a patient with a locally advanced adenoid cystic carcinoma of the right paranasal sinuses, who was treated with interstitial PDT under MR image guidance.…”
Section: Clinical Studiesmentioning
confidence: 99%
“…In the following years, interstitial PDT treatment was developed for tumors >1 cm and later also for metastatic disease in cervical lymph nodes. Image gui-dance was initially performed with grids and preoperative imaging, but subsequently, image guidance similar to the methods used in brachytherapy using open MRI or CT or ultrasound, have proved to be invaluable [13,[18][19][20][21]. The studies following showed similar results concerning CR rates (ranging from 0 % to 77%) [13,[18][19][20][21][22][23][24].…”
Section: Locally Advanced Hnsccmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that it was possible to clearly identify the needles (inc. the tip) during insertion in all 23 treatments and it was possible to guide parallel needle insertions using ultrasound. The study concluded that it was feasible to use 2D-US to guide 'real-time' photodynamic therapy in deep-seated tumours and other malformations and can augment the information from other imaging modalities without affecting the patient's treatment outcome [7].…”
Section: Introductionmentioning
confidence: 99%
“…Short-term treatment for this is with non-steroidal antiinflammatory drugs (NSAIDs) in addition to opiates; most commonly used are codeine phosphate, tramadol and morphine; and for long-term and controlled release fentanyl and buprenorphine patches can be used. The reporting of pain mirrored a temporary rise in white blood cell levels, which followed the induction of tissue necrosis and the generation of acute and chronic inflammatory responses [1,3,7].…”
Section: Introductionmentioning
confidence: 99%